Class Management Strategy in Islamic Religious Education Subjects in Making Effective Teaching and Learning Activities - Hidayah.S, Nurul; Rusli, Rusli; Maudin, Maudin (Journal of English Language and Education, 2025)
This study examines how to effectively teach and learn for class VB pupils at Topa Elementary School in Baubau City using classroom management techniques in Islamic religious education subjects. The fact that certain students continue to perform less well during the teaching and learning process served as the impetus for this investigation. An appropriate classroom management plan must be used to make teaching and learning activities effective if the learning process is to be successful and efficient. This study aims to determine how classroom management strategies are applied in Islamic religious education courses to ensure that teaching and learning activities are successful for class VB students at Topa Elementary School in Baubau City. Identifying the elements that help and impede the use of classroom management strategies in Islamic religious education courses is another goal. This study is qualitative and descriptive, and its data collection techniques include interviews and documentation. Teachers employ a variety of classroom management techniques, according to the study's findings, including adaptable seating arrangements, active learning practices, the use of engaging educational materials, and consistent punishment enforcement.